Citizenship Social Work: A Community Environmental Scan of Re-enfranchisement Social Work Supports after Felony Conviction. Issue 2 (3rd April 2017) - Toft, Jessica; Reierson, Lacey
ABSTRACT: Alexander (2012) argues that the corrections system relegates African American men to permanent second class status. Although social work has advanced the democratic project, African Americans often have had to forge a parallel social assistance system. In a community environmental scan, the authors apply the Citizenship Social Work framework to assess availability of services, supports, and advocacy efforts to address civil, political, social and economic rights for African American men with felony convictions. The authors find that a number of social work services are available, but the majority focus on social and economic rights, rather than civil and political rights, perhaps emphasizing professional service over social justice.